2008
DOI: 10.4137/aci.s396
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Extraction and Reverse-Phase HPLC: Application to Study the Urinary Excretion Pattern of Benzophenone-3 and its Metabolite 2,4-Dihydroxybenzophenone in Human Urine

Abstract: Background:Benzophenone-3 (BZ-3) is a common ultraviolet (UV) absorbing compound in sunscreens. It is the most bioavailable species of all UV-absorbing compounds after topical application and can be found in plasma and urine.Objectives:The aim of this study was to develop a reverse-phase high performance liquid chromatography (HPLC) method for determining the amounts BZ-3 and its metabolite 2,4-dihydroxybenzophenone (DHB) in human urine. The method had to be suitable for handling a large number of samples. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…It is also present in raw [10] and treated domestic wastewater [11], and even in fatty tissues from river and lake fish [10]. Moreover, when applied on the skin, BP-3 is partially absorbed by the human body and excreted as more polar metabolites, such as 2,4-dihydroxybenzophenone (BP-1) and 2,2 -dihydroxy-4-methoxybenzophenone (BP-8) [12,13]. BP-1 and BP-8 are also used as UV absorbers to protect goods against UV radiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is also present in raw [10] and treated domestic wastewater [11], and even in fatty tissues from river and lake fish [10]. Moreover, when applied on the skin, BP-3 is partially absorbed by the human body and excreted as more polar metabolites, such as 2,4-dihydroxybenzophenone (BP-1) and 2,2 -dihydroxy-4-methoxybenzophenone (BP-8) [12,13]. BP-1 and BP-8 are also used as UV absorbers to protect goods against UV radiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…This molecule is used as a sunscreen for skin protection for its ability to absorb and dissipate ultraviolet light [9]. The molecule is highly lipophilic, and is absorbed through human skin; consequently, bioaccumulation may occur in humans, and the compound has been detected in human urine and breast milk [10][11][12][13]. Benzophenone-3, is known to be metabolized by cytochrome P450 and by human liver microsomes.…”
Section: Biotransformation Of Sunscreen Ingredientsmentioning
confidence: 99%
“…For example, after the consumption of a xanthone-rich G. mangostana rind product an increase in the blood serum levels of 15 was identified via LC-MS and remained elevated for 6 hours [35]. Other research has shown that the benzophenone 4,4′-dihydroxybenzophenone-2,4-dinitrophenylhydrazone was orally bioavailable in rats and monkeys as part of preclinical cancer trials [36] and the common sunscreen component, benzophenone-3, is applied topically and its metabolite is detected in urine samples [37]. Based on these previous studies, the benzophenones 4, 5, and 6, as well as, xanthones 15, 16, and 17 are likely bioavailable.…”
Section: Studies Have Established Xanthones As Effective Antimalarialmentioning
confidence: 99%